A revised time-varying mesh stiffness model of spur gear pairs with tooth modifications. (November 2018) - Sun, Yanning; Ma, Hui; Huangfu, Yifan; Chen, Kangkang; Che, LinYang; Wen, Bangchun
Highlights: The revised analytical model considers the effect of lead crowning relief and tip relief. Mesh stiffness model is revised by improving the calculation of each sliced gear pair. The revised model is verified by finite element model considering profile modifications. According to the least mean square error method, the analytical model is further revised. Abstract: Based on the thin slice assumption, a revised time-varying mesh stiffness (TVMS) model of spur gear pairs with tooth modifications is developed. The spur gear is divided into many individual slices along tooth width, and considering the revised fillet-foundation stiffness, the nonlinear contact stiffness, the extended tooth contact and the tooth profile errors, the stiffness of each slice gear pair is figured out. According to the relationship between the deformation and the total stiffness in mesh period, the TVMS of spur gear pairs can be worked out. Meanwhile, relative to the finite element (FE) method, the errors of the proposed method under different modification quantities are discussed. The proposed method is more accurate than those previous methods but there are still some errors. Taking the FE model as a benchmark, the TVMS is further revised based on a simple model updating technique. Based on the revised model, the effects of the tooth width and torque on mesh stiffness are also studied. The result shows that based on the proposed method, the TVMS under any given modification quantities in a suitable range can be calculated accurately.